Crystal structure and tautomerism of Pigment Yellow 138 determined by X-ray powder diffraction and solid-state NMR. (August 2016) - Gumbert, Silke D.; Körbitzer, Meike; Alig, Edith; Schmidt, Martin U.; Chierotti, Michele R.; Gobetto, Roberto; Li, Xiaozhou; van de Streek, Jacco
Abstract: The crystal structure of C.I. Pigment Yellow 138 was determined from X-ray powder diffraction data using real-space methods with subsequent Rietveld refinements. The tautomeric state was investigated by solid-state 1D and 2D multinuclear NMR experiments. In the crystals, the compound exhibits the NH-tautomer with a hydrogen atom situated at the nitrogen of the quinoline moiety. Direct evidence of the presence of the NH-tautomer is provided by 1 H– 14 N HMQC solid-state NMR at very fast MAS. Solid-state dispersion-corrected density functional theory calculations with BLYP-D3 confirm the correctness of the crystal structure and support the NH tautomer. The NH hydrogen atom forms an intramolecular resonance-assisted NH⋯O hydrogen bond to the neighbouring indandione moiety. The indandione moiety is almost coplanar with the quinoline fragment, whereas the phthalimide group forms an angle of 57° with it. Quantum-mechanical calculations show that for an isolated molecule this tautomeric form is by approximately 60 kJ/mol more stable than the OH-form with a hydrogen atom placed at an oxygen atom of the indandione moiety. The out-of-plane rotation of the phthalimide group is not a packing effect, but caused by intramolecular steric hindrance. Graphical abstract: Highlights: The crystal structure is determined from X-ray powder diffraction data. The tautomeric state is determined by extensive solid-state NMR investigations. DFT-D calculations allow the assignment of all 13C SS-NMR signals. DFT-D calculations prove the crystal structure and the tautometric state. P.Y. 138 exhibits the NH tautomeric form.